Contributions of KARDS to Professional Identity of High School Teachers in an EFL Context - Vahid Hassani; Mohammad Khatib (IJET (Indonesian Journal of English Teaching), 2020)
This research aimed at investigating the impacts of knowing, analyzing, recognizing, doing, and seeing (KARDS) on Iranian English as a foreign language (EFL) teachers’ professional identity reconstruction in the context of high schools. Purposive sampling and KARDS questionnaire were used to choose participants and to classify them into a more KARDS-oriented group (n=10) and a less-KARDS oriented group (n=10). The researchers employed pre-course and post-course interview, teacher educator’s and teachers’ reflective journals, and class debate as data gathering tools. Following the pre-course interview, there was an implementation phase of KARDS by means of which teachers were acquainted with it. Then, Grounded Theory was used for data analysis. Findings revealed that there were three big shifts from “uncertainty of practice to certainty of practice”, “the use of fewer macro-strategies to the use of more macro-strategies”, and “linguistic and technical view of language teaching to critical, educational, and transformative view of language teaching” in teachers’ professional identities in both groups. The changes were similar in quality but not in quantity, and they should be incorporated in teacher education programs. The findings may encourage stakeholders to welcome uncertainty and confusion, to underline more macro-strategies, and to take a critical and transformative view of language teaching in language classrooms.